SDG integration into the management of region’s sustainable development - Татьяна Алферова (Вестник Пермского университета: Серия Экономика)
Introduction. A complex and multidimensional strategic management of regional sustainable development is supposed to involve a wide range of participants not only from political, but also from academic and civil circles to prepare and support decisions at the local, national, and global levels. The novelty of the study lies in: a) validating an externally determined approach to set the goals in regional development programs, which is more consistent with the modern pattern of sustainable development; b) substantiating the relevance to observe SDGs to transform the architecture of regional sustainable development programs. The purpose of this work is to develop a methodological approach to integrate the SDGs into regional management policies. Materials and Methods. Based on the analysis and synthesis of scientific information, the author applied the methods of conceptual and functional modeling to design and describe the SDG integration into regional development programs, as well as research integration into preparing political decisions in the field of sustainable development. Results. The proposed methodology is aimed at preparing scientific developments that specifically answer the question of how to achieve systemic implementation of SDGs in the context of regional features and translate this knowledge into a coordinated policy to achieve sustainable development of the region. Conclusions. The proposed developments will eliminate the inconsistencies in the strategic documents on sustainable development of regions, ensure a synergy effect, observe the interests of a wide range of stakeholders at the stage of setting goals, and will also contribute to the real progress towards their achievement. The results of the study may be in demand among the representatives of government and management bodies when preparing the documents aimed at strategic management of sustainable development in Russian regions.